PENINGKATAN PEMAHAMAN FIKIH PADA ANAK DENGAN METODE DEMONSTRASI DI MASA PANDEMI COVID-19 DI TPQ AL-HIKMAH KELURAHAN NGRONGGO KOTA KEDIRI - Muhammad Yahya Khabibi; Agus Miftakus Surur; Agus Subandono (Fenomena, 2021)
This community service aims to introduce Fiqh learning using the demonstration method as an alternative teaching during the Covid-19 pandemic. This community service is based on the Tri Dharma of Higher Education. This community service is a manifestation of the Thematic Real Work Lecture from home (KKN DR) IAIN Kediri program which is carried out virtually and takes into account the applicable health protocols. These activities take various forms, including social media campaigns and teaching. Social media campaigns are used as a form of public education about Covid-19, while teaching is a real form of concern about education during the pandemic. The activity of implementing learning on Fiqh material using the demonstration method was carried out in Ngronggo Village for TPQ al-Hikmah children with the aim of providing an alternative during religious learning during the pandemic. The results of this service show a positive response, where children can receive Fiqh learning and demonstrate so that it can help them to learn Islamic religious education more easily and meaningfully.